An easy approach for constructing vesicles by using aromatic molecules with β-cyclodextrin1. Issue 9 (7th March 2015) - Li, Shangyang; Zhang, Lin; Wang, Bo; Ma, Mingfang; Xing, Pengyao; Chu, Xiaoxiao; Zhang, Yimeng; Hao, Aiyou
<x xml:space="preserve">Abstract</x> Vesicles were formed in aqueous solution using β-cyclodextrin (β-CD) complexes with a series of ultra-small aromatic molecules.